1990
DOI: 10.1016/0014-5793(90)80396-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal 60 Hz sinusoidal magnetic‐field exposure enhances 45Ca2+ uptake in rat thymocytes: dependence on mitogen activation

Abstract: The effect of a 60 Hz sinusoidal magnetic field of nonthermal intensity on Ca2+ metabolism in rat thymic lymphocytes (thymocytes) was assessed in resting cells and in cells activated with the mitogen Concanavalin A (Con A). A 60 min exposure at 37°C to an induced electric field of 1.0 produced an average 2.7‐fold increase in Con A‐dependent 45Ca2+ ‐uptake compared to non‐exposed, isothermal control cells. In contrast, 45Ca2+ uptake remained unaltered during exposure of resting thymocytes. It was also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(90 citation statements)
references
References 14 publications
6
84
0
Order By: Relevance
“…Other studies showed an increase of Ca 2ϩ influx in prestimulated rat thymocytes (86) and lymphocytes (52,53).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 86%
See 2 more Smart Citations
“…Other studies showed an increase of Ca 2ϩ influx in prestimulated rat thymocytes (86) and lymphocytes (52,53).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 86%
“…Experiments with different cell types consistently point to the Ca 2ϩ signaling system as the primary cellular target of MF interactions (5,10,23,52,53,60,69,86,87). In many cases, alternating MFs alone or in combination with static fields increase intracellular Ca 2ϩ , as, for instance, in HL60 cells (10), T-lymphocytes and leukemia cells (60), the human T cell line (Jurkat) (55,56), bone cells (23), pituitary cells (5), and human astrocytoma cells (69).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…However, several investigations have not detected an effect of MF on calcium metabolism or flux in a variety of cell types (11)(12)(13)(14)(15). This (24) reported that calcium uptake in rat lymphocytes was increased by brief exposures to 60-Hz MF only in cells stimulated with the mitogen concanavalin A (ConA). In this study, those lymphocytes least responsive to ConA exhibited the greatest response to MF.…”
mentioning
confidence: 99%
“…Thus, the concentration and/or lifetime of free radicals that escape from the radical pair would increase by exposure to SMF, and free radicals initiate membrane lipids, proteins and DNA damage, and may lead to apoptosis or necrosis [89,90]. The diversity of alterations reported for SMF exposure may be related to varied duration, intensity, tissue penetration, and the type of cells [86,91]. In reproductive tissues, SMF has been shown to modulate the activity of several enzymes related to oxidative stress in the testicles of exposed rats [92].…”
Section: How Does Macs Work?mentioning
confidence: 99%